Effects of grass-red clover silage digestibility and concentrate protein concentration on performance, carcass value, eating quality and economy of finishing Hereford bulls reared in cold conditions - Manninen, Merja; Honkavaara, Markku; Jauhiainen, Lauri; Nykänen, Arja; Heikkilä, Anna-Maija (MTT Agrifood Research Finland, 2011)
The aim of the present experiment was to study the effects of (1) digestibility of grass-red clover silage (GCS) and (2) concentrate protein concentration on the performance, eating quality and economy of Hereford bulls during a six months pre-slaughter period, and reared in cold indoor facilities. Thirty-one bulls with an initial live weight (LW) of 289 kg were selected for a 2 ~ 2 factorial design experiment consisting of two primary growth GCSs harvested at different maturities (in vitro digestible organic matter (OM) in dry matter (DM), D value: Early-cut, E, 750 g kg-1 DM; Late-cut, L, 699 g kg-1 DM) and two concentrate crude protein concentrations (Medium, M, 170 g kg-1 DM; High, H, 210 g kg-1 DM). The concentrate comprised milled barley and pelleted commercial protein compound and was offered daily on average 3.2 kg DM, including 0.45 and 1.13 kg of rapeseed cake in M and H, respectively. Grass-red clover silage was offered ad libitum. The target cold carcass weight was 330 kg.The proportion of concentrate of the total daily DM intake averaged 0.337 during the entire experiment. Treatments had no effect on the daily intake of GCS, total intake of DM, DM intake kg-1 LW0.75 and metabolizable energy averaging 6.0 and 9.4 kg DM, 97.4 g and 109.4 MJ, respectively. The digestibility of dietary OM and neutral detergent fibre was lower (p < 0.05, 0.733 vs. 0.769 and 0.625 vs. 0.665) on diet L than on diet E. The animals on diet E tended to consume daily on average 1.29 kg less (p < 0.10) DM kg-1 net weight gain than those on diet L. The time to achieve the target carcass weight was on average 18 days longer (p < 0.01) on diet L than on diet E. During the entire experiment the LW gain averaged 1795 and 1609 g d-1 (p < 0.01) on diets E and L, respectively. The concentrate protein concentration did not affect animal performance. Treatments had no significant effect on the kill-out proportion, EUROP carcass conformation and carcass fat classification which averaged 537 g kg-1, 6.5 and 3.6, respectively. The eating quality of the tested loins was good. Treatments had only a minor effect on the yield of valuable cuts. It is concluded that the digestibility of silage is important since the early-cut silage improved the growth rate and shortened the finishing period of bulls significantly compared with those fed late-cut silage. The lower yield and, thus, higher unit cost of early.cut silage may, however, invalidate its superiority compared with the late.cut silage. There was no benefit from using concentrate of high protein concentration.
Keywords: Ko; säilörehu; hereford; proteiinit; ruhot; teuraspaino; puna-apila; ruoansulatus; red-clover; silage; protein concentrates; carcass quality; bulls; digestibility; Beef production; concentrate protein concentration; economy; eating quality; silage digestibility